Vibration analysis of air-bearing work-stage under micro-scale effect. (December 2018) - Chen, Dongju; Dong, Lihua; Pan, Ri; Fan, Jinwei; An, Chenhui
Vibration is one of the key factors that influences the ultra-precision machining. Taking the air-bearing work-stage for an example, the vertical vibration of the slide plate will directly affect the surface accuracy of machined parts. There are many factors that affect the vibration of precision machine tools, for example, the fluctuation of gas source, noise, environment, and so on. It will affect the machining accuracy and machining efficiency and cannot work in severe cases. Where the lubrication of the gas film in the air-bearing work-stage is in the micro scale category, its flow characteristics are different from the macroscopic gas flow, and it will also affect the stability of the sliding plate. This paper analyzed the vertical vibration characteristics of the air-bearing work-stage by considering the characteristics of gas film in micro scale when the velocity of the slide plate is 0. Based on the Reynolds equation and the characteristics of gas flow, the stiffness ( K ) and the damping ( C ) of the gas film are obtained by considering different micro factors. The gas film is assumed as the spring system. Then the stiffness and damping of the gas film are taken into the vibration equation of the slide plate. Through solving the vibration equations, the influence of the micro factor of the fluid on the vibration of the slide plate is researched. The results show that when considering the micro factors of the lubrication gas film, the vibration amplitude of slide plate and the frequency at the maximum amplitude are different from the one in macroscopic without considering any micro factors. At the same thickness of the gas film, the influence of the micro factors on the amplitude of slide plate is largest when three micro scale factors (the first order velocity slip, the flow factor Q and the effective viscosity) are considered. With the increase of the film thickness, the micro scale factors have the little effect on the frequency at the maximum amplitude. By analyzing the dimensionless parameters of the experimental signals and the different simulation signals, we found that when the micro-scale factors are considered at the same time, the vibration amplitude of the slide plate and the frequency at the maximum amplitude are closest to the experimental result. It is proved that combined with the micro scale factor, the analysis of dynamic characteristics of air-bearing work-stage is more accurate.